The Financial Risks of Unpaid Caregiving During the COVID-19 Pandemic: Results From a Self-reported Survey in a Canadian Jurisdiction - Husayn Marani; Sara Allin; Sandra McKay; Gregory P. Marchildon (Health Services Insights, 2023)
As health service delivery shifts from institutions to the home, greater care responsibilities are being imposed on unpaid caregivers. However, gaps remain concerning how these responsibilities are contributing to caregivers’ financial risk. This study describes results from an online survey conducted in late-2020 in Ontario, Canada, about the financial risks of unpaid, homebased caregiving throughout the first year of the COVID-19 pandemic. Among 190 caregivers, salient findings include difficulties paying for care expenses after the pandemic was declared than before ( P  = .002); more caregivers retiring or becoming unemployed during the pandemic than before ( P  = .013); and a significant relationship between paying out-of-pocket for a home care worker and experiencing a decrease in the availability of such support during the pandemic ( P  = .029). Overall, the financial stressors of caregiving during the pandemic contributed negatively to caregivers’ mental health, with 64.2% noting could be partly offset by greater government and employment-based assistance in managing care expenses and productivity losses. Findings from this study will better inform policies that aim to protect unpaid caregivers from financial risk in pandemic recovery efforts and beyond. Results may also be useful in other welfare states where unpaid caregivers provide the majority of home care services.